Navigating Ethical Dilemmas in Supply Chain Management: Insights from Practitioners - A Sigit Pramono Hadi; Cahyatih Kumandang; Ruslaini Ruslaini (LPPM STIE Kasih Bangsa, 2024)
This qualitative research study delves into the complex landscape of ethical decision-making within supply chain management, drawing insights directly from industry practitioners. With a focus on identifying, analyzing, and navigating ethical dilemmas, the study employs in-depth interviews and thematic analysis to elucidate the multifaceted challenges faced by professionals in this field. Through rich narratives and thematic synthesis, the research explores the nuanced perspectives, strategies, and coping mechanisms employed by practitioners when encountering ethical conflicts. Findings underscore the significance of fostering a culture of transparency, accountability, and ethical awareness within supply chains. Furthermore, the study sheds light on the importance of proactive measures, collaborative approaches, and continuous dialogue in addressing ethical concerns effectively. The insights gleaned offer valuable implications for both theory and practice, contributing ing disto the ongocourse on ethics in supply chain management.